(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The comparative study of growth and efficiency of Nepeta cataria var. citriodora Dum. and Elsholtzia stauntonii Benth. on subirrigation in a Steppe zone and Southern coast of Crimea is given.